THE CONSTRUCTION OF GENDERS IN PHISICAL EDUCATION CLASSES: POLICY STUDY HISTORICAL, SOCIAL AND PEDAGOGICAL (Fiep Bulletin - online, 2010)
This paper analyses gender issues through a historical, social and pedagogic perspective, evaluates educational influence on male and femaleness conception and defines the role of the physical education teacher on establishing coeducation as a tool to gradually promote equality between sexes.
Keywords: Physical Education; gender; coeducation